Malaysia’s deep tropical ruminant production system can feed the world. - Davis, Mohd Peter; Yogendran, N. (2009)
Malaysia’s `Deep Tropical’ ruminant production system is a radical departure from traditional European grazing systems which have repeatedly failed during 450 years of colonial rule and 50 years of independence. Despite a modern industrialized economy and a tiny population of 27 million to feed, Malaysia has made no progress in food self-sufficiency in the last 25 years and only produces 5% its dairy products, 8% mutton and 23% beef. Instead of changing the genetics of ruminants to cope with the disease load and heat stress of the humid tropics, Deep Tropical is based on the world’s most productive breeds housed in climate controlled barns and fed 35 day old fresh cut grass from luxuriant grass farms. Commercial pilot studies using the GIFT farming system with Dorper sheep and Jersey cows indicate a 3 fold higher production per hectare of land compared to the best New Zealand grazing farms. A US$15m Malaysian dairy with 100 hectare grass farm and climate barns for pregnant Jersey cows air freighted from Australia has recently been established in 9 months with plans for 1200 calving and milking cows by early 2009. Similar farms for 25,000 sheep are being negotiated. Given the political will, it is technically feasible to make Malaysia self sufficient in milk, lamb and beef within 10 years. Deep Tropical has the potential to be replicated throughout Borneo and other rainforest climates including the Amazon and indeed throughout the dry topics and even deserts as abundant supplies of nuclear desalinated water come on stream over the next 10-50 years.